أسباب الفرقة في الأسرة المسلمة وعلاجها من منظور إسلامي : بانكوك نموذجا - سينج ساوانج، شادا (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2007)
This thesis examines the pressing issue of legal separation (Furqah) among Muslim married couples in Bangkok, Thailand. As a minority group in a predominantly Buddhist country, cases of separation and divorce among Muslim married couples have been rising. This phenomenon is a clearly a cause for concern. The thesis discusses the common causes for this alarming development and provides possible remedies to check this phenomenon from becoming a crisis for the beleaguered Muslim community in Thailand. The thesis relies on the views of Thai Muslim syarie judges and lawyers as well as scholars in putting forward a critical examination of the Muslim community in Asia.